Optimization of Multiple Micro Pumps to Maximize the Flow Rate and Minimize the Flow Pulsation. (2016) - Dhananchezhiyan, P.; Hiremath, Somashekhar S.
Abstract: In recent years, micro pump plays a significant role in many fields, specifically in chemical, medical, and thermal managements. Since there are distinct requirements in each field, several types of micro pumps have been designed to meet those requirements. Fluid flow from these micro-pumps is delivered in a series of small discrete volumes, which make up a pulsating flow. In order to reduce the pulsating flow, the multiple micro-pumps should be actuated in parallel. Thus, in the present work, two piezo-electrical diaphragm type micro-pumps are operated in parallel with a microcontroller based sequential switching to maximize the flow rate and minimize the flow pulsation. Micro-pumps are switched in different phase shifts to study the flow pattern. The flow pulsation is measured in terms of pressure pulsation using pressure transducer. Flow pulsations are recorded for various drive frequencies in the range of 10Hz to 40Hz and for peak-to-peak drive voltage in range of 100 - 250V. It is observed that the flow pulsation for both micro pumps is minimum at higher frequencies and lower drive voltages. Also the flow rate of combined micro pumps with and without offset is precisely measured and reported in the paper.